Sprayed concrete with high strength and low rebound rate and preparation method thereof

Through the cross-linking network system of composite modified fibers and modified montmorillonite, combined with liquid SiO2, the shortcomings of sprayed concrete in high strength and durability are solved, and high strength, low rebound rate and excellent durability are achieved. tunnel lining material in complex environments.

CN119306444AActive Publication Date: 2025-01-14PEARL RIVER HYDRAULIC RES INST OF PEARL RIVER WATER RESOURCES COMMISSION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411473257.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing spray concrete preparation methods ignore the rebound rate when pursuing high strength and ignore the durability when reducing the rebound rate. It is difficult to meet the structural service life and deformation protection requirements in the complex environment of spray concrete.

Method used

Compound modified fibers and modified montmorillonite are prepared through acid dissolution, cationic intercalation and other steps, combined with liquid SiO2, to form a cross-linking network system, improve the bonding strength, durability and crack resistance of sprayed concrete, and reduce the return Bullet rate.

Benefits of technology

The sprayed concrete with high strength, low rebound rate and high durability is achieved, which significantly improves its structural stability and service life in complex environments and meets the high performance requirements of tunnel lining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306444A_ABST
    Figure CN119306444A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete preparation, in particular to high-strength and low-resilience sprayed concrete and a preparation method thereof. The sprayed concrete is prepared from the composite modified fibers and the modified montmorillonite, so that the prepared concrete has high crack resistance and high durability, and the characteristics of small particle size and large specific surface area of the liquid SiO2 are utilized, so that the rebound rate of the sprayed concrete is directly reduced, and the durability of the sprayed concrete is improved. When the modified montmorillonite is uniformly dispersed into a cross-linked network system of the composite modified fibers and the modified montmorillonite, the chemical bonding capability of the modified montmorillonite and the composite modified fibers can be enhanced, the rebound rate of the sprayed concrete is further reduced, and the crack resistance and durability of the sprayed concrete are improved, so that the structural deformation of a tunnel can be better limited, and the service life of the tunnel is prolonged. And the service life of the tunnel lining in a complex environment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to high-strength, low-rebound rate shotcrete and a preparation method thereof. Background Art

[0002] Shotcrete is widely used in railway, highway, water conservancy, mining and other industries. Shotcrete uses air pressure to spray high-slump concrete at high speed onto the sprayed surface, instantly forming a permanent lining concrete. High-performance shotcrete needs to have good pumpability and sprayability, high strength and excellent durability. Good sprayability is the key to reducing the rebound rate of concrete and increasing the thickness of a single spray, while high strength and durability are to ensure its protective effect on the deformation of tunnel surrounding rocks in complex environments and to improve its structural service life. Shotcrete is composed of cement, mineral admixtures, admixtures, water, etc. It has special requirements for water-cement ratio, amount of cementitious materials, sand ratio, etc. The working performance and durability of shotcrete obtained by different compositions, proportions and preparation methods vary greatly. Therefore, it is very important to select the composition, proportion and preparation method of shotcrete.

[0003] The shotcrete disclosed in patent document CN 117886575 mainly improves its strength and reduces its rebound rate by adding modified additives and functional agents; while the shotcrete preparation method disclosed in patent document CN 118084437 improves the dispersion effect of steel fibers and reduces its rebound rate by modifying the accelerating agent. However, the defects of the shotcrete preparation method in the prior art are that, on the one hand, only the high strength of the shotcrete is considered, but its rebound rate is not considered; on the other hand, the low rebound rate of the shotcrete is considered, but its durability is not involved.

[0004] Therefore, seeking a new method for preparing shotcrete to solve the above-mentioned defects is a problem that needs to be solved urgently. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a high-strength, low-rebound shotcrete and a preparation method thereof. The present invention prepares shotcrete by composite modified fiber and modified montmorillonite, so that the prepared concrete has high crack resistance and high durability. The present invention also simultaneously utilizes the characteristics of liquid SiO2 with small particle size and large specific surface area, which not only directly reduces the rebound rate of shotcrete, but also enhances the chemical bonding ability of modified montmorillonite and composite modified fiber when it is evenly dispersed in the cross-linked network system of composite modified fiber and modified montmorillonite, further reduces the rebound rate of shotcrete, improves its crack resistance and durability, thereby better limiting the deformation of tunnel structure and improving the service life of tunnel lining under complex environment.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A high-strength, low-rebound shotcrete comprises the following components by mass: 420-450 parts of ordinary Portland cement, 10-60 parts of liquid nano-SiO2, 850-950 parts of fine aggregate, 700-800 parts of coarse aggregate, 30-80 parts of composite modified fiber, 100-200 parts of modified montmorillonite, 5-10 parts of coupling agent, 5-8 parts of cross-linking agent, 10-30 parts of water reducer, 3-5 parts of cellulose and 170-190 parts of water.

[0008] Preferably, the modified montmorillonite is prepared by the following steps:

[0009] S11. Acid hydrolysis: immerse 250-300 parts by mass of montmorillonite in a concentrated hydrochloric acid solution having a concentration of 0.5-2 mol / L for 1-2 h;

[0010] S12. Cationic intercalation: The montmorillonite treated in step S11 is immersed in a 3-4 mol / L FeCl3 solution, allowed to stand for 1-2 hours, and then taken out and calcined at 1000-1200°C for 3-4 hours to obtain modified montmorillonite.

[0011] Preferably, the composite modified fiber is a mixture of basalt fiber: PE fiber: glass fiber in a mass ratio of 2-3: 0.5-1: 1-2.

[0012] Preferably, the composite modified fiber is prepared by the following steps:

[0013] S21. Mixing basalt fiber, PE fiber and glass fiber into a fiber bundle according to a set ratio;

[0014] S22. 40-90 parts by mass of the fiber bundle are immersed in an aqueous ammonia solution having a concentration of 1-3 mol / L, and then taken out at 40-50 ° C for 0.5-2h and dried;

[0015] S23. Immerse 40-90 parts by mass of the fiber bundle treated in step S22 in 100-150 parts of bisphenol A epoxy resin for 1-2 hours and then take it out to obtain the composite modified fiber.

[0016] Preferably, the strength grade of the ordinary Portland cement is ≥42.5; the liquid nano-SiO2 is spherical particles with a particle size of 50-200nm.

[0017] Preferably, the coupling agent is a mixture of γ-methacryloxypropyltrimethoxysilane, 3-epoxypropyltriethoxysilane, and isopropyl tri(dilauroyl)titanate in a mass ratio of 3-4:1-3:1; and the cross-linking agent is a mixture of hexamethylene diisocyanate and diethylenetriamine in a mass ratio of 2:1.

[0018] Preferably, the diameter of the basalt fiber is 100-400 μm, the elastic modulus is 8000-10000 MPa, and the tensile strength is 3500-4500 MPa; the diameter of the glass fiber is 200-300 μm, the elastic modulus is 70-85 GPa, and the tensile strength is 2000-3000 MPa; the diameter of the PE fiber is 100-400 μm, the elastic modulus is 20-30 GPa, and the tensile strength is 3000-4000 MPa.

[0019] Preferably, the fine aggregate is artificial sand with a fineness modulus of 2.5-2.8; the coarse aggregate is natural pumice with a particle size of 5-10 mm.

[0020] Preferably, the cellulose is one of carboxymethyl cellulose and hydroxypropyl cellulose; the viscosity of the cellulose is 50,000-100,000.

[0021] A method for preparing high-strength, low-rebound shotcrete, used for preparing the shotcrete, comprises the following steps:

[0022] S1. Weigh the composite modified fiber, modified montmorillonite, coupling agent and crosslinking agent according to the set ratio, pour them into a blender and mix for 60-90s;

[0023] S2. Weigh the corresponding proportions of ordinary Portland cement, liquid nano-SiO2, fine aggregate, coarse aggregate, and cellulose, mix them evenly, and add them to a mixer and stir for 1-2 minutes;

[0024] S3. Weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the high-strength, low-resilience shotcrete.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention utilizes composite modified fibers to improve the bonding strength of shotcrete, thereby reducing the rebound rate of shotcrete;

[0027] 2. The present invention modifies montmorillonite by cationic intercalation, thereby increasing the interlayer spacing and porosity of montmorillonite and improving its adsorption capacity. When applied to concrete, it can effectively fill the pore structure of concrete, thereby improving the durability of concrete. In addition, after calcination, the modified montmorillonite partially decomposes the interlayer structure and releases active MgO, which continuously absorbs water during later use and is converted into Mg(OH)2 and filled in the concrete system, thereby further improving the compactness of the concrete.

[0028] 3. The present invention complements the advantages of different fibers by compounding composite fiber bundles, thereby improving the tensile strength of the overall fiber bundle, and further improving the dispersibility of the composite fiber in concrete. At the same time, the modified fiber bundle and montmorillonite can also form a cross-linked network system to further improve the compactness of the shotcrete, thereby greatly improving its durability;

[0029] 4. The present invention utilizes the characteristics of liquid SiO2, which has a small particle size and a large specific surface area, to not only directly increase the instantaneous adhesion of the shotcrete, but also, when it is evenly dispersed in the cross-linked network system of the composite modified fiber and the modified montmorillonite, enhance the chemical bonding ability of the modified montmorillonite and the composite modified fiber, further reduce the rebound rate of the shotcrete, improve its crack resistance and durability, thereby better limiting the deformation of the tunnel structure and increasing the service life of the tunnel lining in a complex environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a process flow chart for preparing the high-strength, low-resilience shotcrete of the present invention;

[0031] Figure 2 This is a process flow chart of the preparation of the modified montmorillonite of the present invention;

[0032] Figure 3 The present invention is a process flow chart for preparing the composite modified fiber. DETAILED DESCRIPTION

[0033] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] See also Figure 1-3 , the present invention provides a technical solution:

[0035] Example 1

[0036] A method for preparing high-strength, low-rebound shotcrete:

[0037] S1. Weigh the composite modified fiber, modified montmorillonite, coupling agent, and crosslinking agent according to the set ratio, pour them into a blender and mix for 60s;

[0038] S2. Weigh the corresponding proportions of ordinary Portland cement, liquid nano-SiO2, fine aggregate, coarse aggregate, and cellulose, mix them evenly, and add them to a mixer and stir for 1 min;

[0039] S3. Weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the high-strength, low-resilience shotcrete.

[0040] In the above process, the amount of each raw material is as follows:

[0041] Components Dosage(kg) Composite modified fiber 3 Modified montmorillonite 10 Coupling agent 0.5 Crosslinking agent 0.5 Ordinary Portland Cement 42 <![CDATA[Liquid nano-SiO2]]> 1 Fine aggregate (artificial sand) 85 Coarse aggregate (natural pumice) 70 Cellulose (Carboxymethyl Cellulose) 3 Water reducing agent (polycarboxylate water reducing agent) 10 water 170

[0042] In the above process, the strength grade of the ordinary Portland cement is ≥42.5;

[0043] The liquid nano-SiO2 is spherical particles with a particle size range of 50-200nm;

[0044] The coupling agent is a mixture of γ-methacryloxypropyltrimethoxysilane, 3-epoxypropyltriethoxysilane and isopropyl tri(dilauroyl)titanate in a mass ratio of 3:1:1;

[0045] The cross-linking agent is a mixture of hexamethylene diisocyanate and diethylenetriamine in a mass ratio of 2:1;

[0046] The fine aggregate is artificial sand with a fineness modulus of 2.5;

[0047] The coarse aggregate is natural pumice with a particle size of 5-10 mm;

[0048] The viscosity of the cellulose is 50,000;

[0049] The composite modified fiber is a mixture of basalt fiber: PE fiber: glass fiber in a mass ratio of 2:0.5:1;

[0050] The basalt fiber has a diameter of 100 μm, an elastic modulus of 8000 MPa, and a tensile strength of 3500 MPa;

[0051] The diameter of the glass fiber is 200 μm, the elastic modulus is 70 GPa, and the tensile strength is 2000 MPa; the diameter of the PE fiber is 100 μm, the elastic modulus is 20 GPa, and the tensile strength is 3000 MPa;

[0052] The composite modified fiber is prepared by the following steps:

[0053] S21. Mixing basalt fiber, PE fiber and glass fiber into a fiber bundle in a ratio of 2:0.5:1;

[0054] S22. The fiber bundle of 4kg was immersed in an aqueous ammonia solution having a concentration of 3mol / L, and then allowed to stand at 40°C for 0.5h and then taken out and dried;

[0055] S23. Immerse 4 kg of the fiber bundle treated in step S22 in 10 kg of bisphenol A epoxy resin for 1 hour and then take it out to obtain the composite modified fiber;

[0056] The bisphenol A epoxy resin was purchased from Hubei Shixing Chemical Co., Ltd.

[0057] The modified montmorillonite is prepared by the following steps:

[0058] S11. Acid hydrolysis: immerse 25 kg of montmorillonite in a 2 mol / L concentrated hydrochloric acid solution for 1 h;

[0059] S12. Cationic intercalation: The montmorillonite treated in step S11 was immersed in a 3 mol / L FeCl3 solution, allowed to stand for 2 h, and then taken out and calcined at 1000°C for 4 h to obtain modified montmorillonite.

[0060] Example 2: Example 2 is different from Example 1 in that, in Example 2, the composite modified fiber is a mixture of basalt fiber: PE fiber: glass fiber in a mass ratio of 3:0.5:2, and the remaining steps are exactly the same in Example 2 and Example 1.

[0061] Example 3: Example 3 is different from Example 1 in that, in Example 3, the composite modified fiber is prepared by the following steps:

[0062] S21. Mixing basalt fiber, PE fiber and glass fiber into a fiber bundle in a ratio of 2:0.5:1;

[0063] S22. The fiber bundle of 4 kg was immersed in an aqueous ammonia solution having a concentration of 1 mol / L, and then taken out at 40 ° C for 2 h and dried;

[0064] S23. Immerse 4 kg of the fiber bundle treated in step S22 in 10 kg of bisphenol A epoxy resin for 1.5 hours and then take it out to obtain the composite modified fiber;

[0065] The remaining steps are exactly the same in Example 3 and Example 1.

[0066] Example 4: Example 4 is different from Example 1 in that, in Example 4, the modified montmorillonite is prepared by the following steps:

[0067] S11. Acid hydrolysis: 25 kg of montmorillonite was immersed in a concentrated hydrochloric acid solution with a concentration of 0.5 mol / L for 2 h;

[0068] S12. Cationic intercalation: The montmorillonite treated in step S11 was immersed in a 4 mol / L FeCl3 solution and allowed to stand for 1 h before being taken out and calcined at 1200 ° C for 3 h to obtain a modified montmorillonite;

[0069] The remaining steps are exactly the same in Example 4 and Example 1.

[0070] Example 5: Example 5 is different from Example 1 in that the amount of each component in Example 5 is as follows:

[0071] Components Dosage(kg) Composite modified fiber 8 Modified montmorillonite 20 Coupling agent 0.5 Crosslinking agent 0.5 Ordinary Portland Cement 42 <![CDATA[Liquid nano-SiO2]]> 1 Fine aggregate (artificial sand) 85 Coarse aggregate (natural pumice) 70 Cellulose (Carboxymethyl Cellulose) 3 Water reducing agent (polycarboxylate water reducing agent) 10 water 170

[0072] The remaining steps are exactly the same in Example 5 and Example 1.

[0073] Example 6: Example 6 is different from Example 1 in that the amounts of the components in Example 6 are as follows:

[0074]

[0075]

[0076] The remaining steps are exactly the same in Example 6 and Example 1.

[0077] Example 7: Example 7 is different from Example 1 in that the amount of each component in Example 7 is as follows:

[0078] Components Dosage(kg) Composite modified fiber 3 Modified montmorillonite 10 Coupling agent 0.5 Crosslinking agent 0.5 Ordinary Portland Cement 42 <![CDATA[Liquid nano-SiO2]]> 6 Fine aggregate (artificial sand) 85 Coarse aggregate (natural pumice) 70 Cellulose (Carboxymethyl Cellulose) 3 Water reducing agent (polycarboxylate water reducing agent) 10 water 170

[0079] The remaining steps are exactly the same in Example 7 and Example 1.

[0080] Comparative Example:

[0081] Comparative Example 1: Comparative Example 1 is different from Example 1 in that, in Comparative Example 1, some of the raw material components for preparing shotcrete described in Example 1 are omitted, thereby omitting the use of composite modified fibers, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.

[0082] Comparative Example 2: Comparative Example 2 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 2, thereby omitting the use of modified montmorillonite, and the remaining steps are exactly the same in Comparative Example 2 and Example 1.

[0083] Comparative Example 3: Comparative Example 3 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 3, thereby omitting the use of liquid nano-SiO2, and the remaining steps are exactly the same in Comparative Example 3 and Example 1.

[0084] Comparative Example 4: Comparative Example 4 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 4, thereby omitting the use of modified montmorillonite and composite modified fiber, and the remaining steps are exactly the same in Comparative Example 4 and Example 1.

[0085] Comparative Example 5: Comparative Example 5 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 5, thereby omitting the use of modified montmorillonite, composite modified fiber, and liquid nano-SiO2. The remaining steps are exactly the same in Comparative Example 5 and Example 1.

[0086] According to the experimental requirements of GB 50204-2015, GB / T 50081-2019, GB / T 50082-2009, GB / T50081-2002, and JGJ / T 23-2011, the compressive strength, bending resistance, one-time spraying thickness, and rebound rate of the shotcrete prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1:

[0087] Table 1. Concrete performance test data

[0088]

[0089]

[0090] Referring to the above content, it can be seen that the high-strength, low-rebound shotcrete provided by the present invention has a compressive strength of ≥72.3MPa, and a maximum of 82.1MPa; a flexural strength of ≥9.2MPa, and a maximum of 11.2MPa, and the concrete has no strength shrinkage phenomenon during long-term use, and its performance is far superior to that of ordinary concrete, meets the technical requirements of shotcrete, and also meets the high performance requirements of tunnel engineering for concrete; secondly, the rebound rate is less than 6%, and the one-time spraying thickness is ≥22cm, which further illustrates that the shotcrete prepared by the present application is a low-rebound performance, excellent and stable concrete material, which can be industrially produced on a large scale;

[0091] At the same time, as shown in Table 1, the significant difference in performance between Example 1 of the present application and Comparative Examples 1, 2, 4, and 5 strongly proves that the present invention increases the interlayer spacing and porosity of montmorillonite and improves its adsorption capacity by modifying montmorillonite through cationic intercalation. When applied to concrete, it can effectively fill the pore structure of concrete, thereby improving the durability of concrete. At the same time, by compounding the composite fiber bundle, the advantages of different fibers are complemented, thereby improving the tensile strength of the overall fiber bundle, and then improving the dispersibility of the composite fiber in concrete. The modified fiber bundle and montmorillonite can also form a cross-linked network system to further improve the compactness of the shotcrete, thereby greatly improving its mechanical properties and durability.

[0092] The significant difference in performance between Example 1 and Comparative Examples 3 and 4 proves that the present invention utilizes the characteristics of small particle size and large specific surface area of ​​liquid SiO2, which not only directly reduces the rebound rate of shotcrete, but also, when it is evenly dispersed in the cross-linked network system of composite modified fibers and modified montmorillonite, can further reduce the rebound rate of shotcrete by enhancing the chemical bonding ability of modified montmorillonite and composite modified fibers, improve its crack resistance and durability, thereby better limiting the deformation of tunnel structure and increasing the service life of tunnel lining in complex environments.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength, low-rebound shotcrete, characterized in that: The composition includes the following components by mass: 420-450 parts of ordinary Portland cement, 10-60 parts of liquid nano-SiO2, 850-950 parts of fine aggregate, 700-800 parts of coarse aggregate, 30-80 parts of composite modified fiber, 100-200 parts of modified montmorillonite, 5-10 parts of coupling agent, 5-8 parts of cross-linking agent, 10-30 parts of water reducer, 3-5 parts of cellulose and 170-190 parts of water.

2. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The modified montmorillonite is prepared by the following steps: S11. Acid hydrolysis: immerse 250-300 parts by mass of montmorillonite in a concentrated hydrochloric acid solution having a concentration of 0.5-2 mol / L for 1-2 h; S12. Cationic intercalation: The montmorillonite treated in step S11 is immersed in a 3-4 mol / L FeCl3 solution, allowed to stand for 1-2 hours, and then taken out and calcined at 1000-1200°C for 3-4 hours to obtain modified montmorillonite.

3. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The composite modified fiber is a mixture of basalt fiber: PE fiber: glass fiber in a mass ratio of 2-3: 0.5-1: 1-2.

4. The high-strength, low-resilience shotcrete according to claim 3, characterized in that: The composite modified fiber is prepared by the following steps: S21. Mixing basalt fiber, PE fiber and glass fiber into a fiber bundle according to a set ratio; S22. 40-90 parts by mass of the fiber bundle are immersed in an aqueous ammonia solution having a concentration of 1-3 mol / L, and then taken out at 40-50 ° C for 0.5-2h and dried; S23. Immerse 40-90 parts by mass of the fiber bundle treated in step S22 in 100-150 parts of bisphenol A epoxy resin for 1-2 hours and then take it out to obtain the composite modified fiber.

5. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The strength grade of the ordinary Portland cement is ≥42.5; the liquid nano-SiO2 is spherical particles with a particle size of 50-200nm.

6. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The coupling agent is a mixture of γ-methacryloxypropyltrimethoxysilane, 3-epoxypropyltriethoxysilane and isopropyl tri(dilauroyl)titanate in a mass ratio of 3-4:1-3:1; the crosslinking agent is a mixture of hexamethylene diisocyanate and diethylenetriamine in a mass ratio of 2:

1.

7. The high-strength, low-rebound shotcrete according to claim 4, characterized in that: The diameter of the basalt fiber is 100-400 μm, the elastic modulus is 8000-10000 MPa, and the tensile strength is 3500-4500 MPa; the diameter of the glass fiber is 200-300 μm, the elastic modulus is 70-85 GPa, and the tensile strength is 2000-3000 MPa; the diameter of the PE fiber is 100-400 μm, the elastic modulus is 20-30 GPa, and the tensile strength is 3000-4000 MPa.

8. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The fine aggregate is artificial sand with a fineness modulus of 2.5-2.8; the coarse aggregate is natural pumice with a particle size of 5-10 mm.

9. The high-strength, low-resilience shotcrete according to claim 1, characterized in that: The cellulose is one of carboxymethyl cellulose and hydroxypropyl cellulose; the viscosity of the cellulose is 50,000-100,000.

10. A method for preparing high-strength, low-rebound shotcrete, used for preparing the shotcrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh the composite modified fiber, modified montmorillonite, coupling agent, and crosslinking agent according to the set ratio, pour them into a blender and mix for 60-90s; S2. Weigh the corresponding proportions of ordinary Portland cement, liquid nano-SiO2, fine aggregate, coarse aggregate, and cellulose, mix them evenly, and add them to a mixer and stir for 1-2 minutes; S3. Weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the high-strength, low-resilience shotcrete.

Citation Information

Patent Citations

  • Novel cement-based particle blend non-combustible light composite heat preservation board and processing method thereof

    CN110342872A

  • Multi-mineral immobilization system based on solid waste and preparation method of multi-mineral immobilization system

    CN118529956A

  • Suspensions with high storage stability, comprising an aqueous silicate solution and a filler material

    US6372694B1

  • Sprayable cementitious composition

    WO2021167635A1